Bioinformatics: Challenges in Integrating Biological Information - Sardi, Arif (Jurnal Biologi Tropis, 2022)
Bioinformatics has become a buzzword in today’s world of science. About twenty or thirty years ago, people saw biology and computer science as two completely different fields. However, at present, it seems that a new bridge has been built that connects these two fields, and this new field is called bioinformatics. Bioinformatics is an challenging and exciting new multidisciplinary field. This field combines methods of statistics, mathematics, computer science and information technology to solve problems based on biological data. Advances in experimental technology have generated large amounts of data. Therefore, managing and extracting useful information from these sources is essential if we are to discover new knowledge to advance our understanding of life. In this article, we try to discuss what is bioinformatics?, The basic knowledge needed to understand bionformatics and the reasons that are very important for biologists to learn and apply bioinformatics. In addition, we also discuss an introduction to biological terminology that will be widely used in the field of bioinformatics. We are confident that this review will provide valuable insights and serve as a starting point for researchers to become acquainted with and study bioinformatics.